Broadband Characteristics of Chaotic Pulse Trains Associated With Sequential Dart Leaders in a Rocket‐Triggered Lightning Flash. Issue 7 (5th April 2019) - Pu, Yunjiao; Qie, Xiushu; Jiang, Rubin; Sun, Zhuling; Liu, Mingyuan; Zhang, Hongbo
Abstract: Based on simultaneous measurements of fast E‐field change, very high frequency radiation and channel mapping, channel base current, and high‐speed video, the characteristics of chaotic pulse trains (CPTs) during propagation of dart leaders in a rocket‐triggered lightning were analyzed. The triggered lightning involved 16 subsequent leader‐return strokes traversing in the same grounding channel. At least five dart leaders showed significant CPT signals during its propagation, with much larger intensity than that in normal leader stage at broadband of low‐frequency–medium‐frequency, very high frequency, and visible light band. All CPTs occurred in the final stage of the leader development, within 150 μs prior to the return strokes. The leader velocity and the charge transfer are both related to the instantaneous intensity of CPT, but the relationship is not always solid when the two parameters are considered individually. Nevertheless, the large product of return stroke charge to 1 ms and the velocity of the leader (QV) could be a reliable proxy/indicator for CPT. All CPTs correspond to a larger local QV with a threshold higher than 1 × 10 7 C · m/s when CPT is determined as chaotic electric field pulses with magnitude larger than 3 std of the magnitude of E‐fluctuation waveform of the whole flash. Key Points: Multiple parameters (intensity, velocity, and charge) related to CPT are analyzed based on E‐field, optical, VHF, and current measurements CPT is characterized by much higher radiation intensity at broadband of radio frequency and optical band than normal leader stage A large product of RS charge to 1 ms (a proxy for leader charge) and the instantaneous leader velocity (Q · V) is a reliable indicator of CPT